"Evolving Trends in Pancreatic Cystic Tumors: A 3-Decade Single-Center Experience With 1290 Resections". Issue 3 (4th March 2023) - Roldán, Jorge; Harrison, Jon M.; Qadan, Motaz; Bolm, Louisa; Baba, Taisuke; Brugge, William R.; Casey, Brenna W.; Krishnan, Kumar; Mino-Kenudson, Mari; Pitman, Martha B.; Kambadakone, Avinash; Ferrone, Cristina R.; et al.
Abstract : Objective: The aim of this study was to describe our institutional experience with resected cystic tumors of the pancreas with emphasis on changes in clinical presentation and accuracy of preoperative diagnosis. Summary Background Data: Incidental discovery of pancreatic cystic lesions has increased and has led to a rise in pancreatic resections. It is important to analyze surgical outcomes from these procedures, and the prevalence of malignancy, pre-malignancy and resections for purely benign lesions, some of which may be unintended. Methods: Retrospective review of a prospective database spanning 3 decades. Presence of symptoms, incidental discovery, diagnostic studies, type of surgery, postoperative outcomes, and concordance between presumptive diagnosis and final histopathology were recorded. Results: A total of 1290 patients were identified, 62% female with mean age of 60 years. Fifty-seven percent of tumors were incidentally discovered. Ninety-day operative mortality was 0.9% and major morbidity 14.4%. There were 23 different diagnosis, but IPMN, MCN, and serous cystadenoma comprised 80% of cases. Concordance between preoperative and final histopathological diagnosis increased by decade from 45%, to 68%, and is presently 80%, rising in parallel with the use of endoscopic ultrasound, cytology, and molecular analysis. The addition of molecular analysis improved accuracy to 91%. Of misdiagnosed cases, half were purely benign and taken to surgery with the presumption of malignancy or premalignancy. The majority of these were serous cystadenomas. Conclusions: Indications and diagnostic work-up of cystic tumors of the pancreas have changed over time. Surgical resection can be performed with very low mortality and acceptable morbidity and diagnostic accuracy is presently 80%. About 10% of patients are still undergoing surgery for purely benign lesions that were presumed to be malignant or premalignant. Further refinements in diagnostic tests are required to improve accuracy.